Analisis Manajemen Breeding Sapi Madura Betina Grade 1 dan 2 Berbasis Kearifan Lokal di Wilayah Sumber Bibit Pamekasan - Sari, Ayu Mufidah Kartika; Mudawamah; Humaidah, Nurul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the management of Madura cows, grades 1 and 2, based on local wisdom in the breeding source area of Waru Subdistrict, Pamekasan Regency. The method used was a case study. Data were obtained through direct interviews with 36 farmers who met the following criteria: keeping at least 2 Madura cows of grade 1 and 2 females, cattle aged 24-36 months, in good health, who had given birth, and who were not pregnant. Data were analyzed using the Chi-Square Test and was analyzed descriptively.. The results showed that the breeding management aspects of feed, housing, and mating systems for grade 1 and 2 cows were not significantly different (P>0.05). However, on average, grade 1 breeding management tended to be better than grade 2. Average forage feeding was 29.89±1.65 kg/head/day (grade 1) and 25.06±1.81 kg/head/day (grade 2). The mean supplementary feeding of Tajin was 3.11 kg/head/day (grade 1) and 2.06 kg/head/day (grade 2). Grade 1 (88.89%) and grade 2 (72.22%) farmers used wood-based stage cages with tile roofs and areas, as specified by SNI. Natural mating was the leading choice of grade 1 (68.42%) and grade 2 (64.71%) breeders. In comparison, Artificial Insemination was the leading choice of grade 1 (31.58%) and grade 2 (35.29%) breeders. The study concluded that the components of grade 1 and 2 breeding management, based on local wisdom, are similar; however, there are differences in the quantity of treatment. The forage feed management aspect of grade 1 was 16.15% higher than grade 2. Supplementary feed Tajin grade 1 was 33.76% more than grade 2. The majority of grade 1 and 2 farmers used wood-based stage cages with tile roofs, and the area was by SNI. The ratio of the natural breeding system in grade 1 and grade 2 was 7.68%, and the AI was 19.99%.